A new species of soft-winged flower beetles of the genus Platyebaeus Wittmer, 1995 (Coleoptera, Cleroidea, Malachiidae) from Philippines - Tshernyshev, Sergei E. (Zootaxa, 2015)
A new malachiid species of the genus Platyebaeus Wittmer is described: P. quirinicus sp. n., from the Sierra Madre mountain range in Quirino province, Luzon Island, Philippines. Figures of male habitus, elytral apical third profile, genitalia, and a map showing the type locality are given for the new species. A determination key to the 3 species belonging to Platyebaeus is also provided.